2017
DOI: 10.1016/j.eurpsy.2017.01.1328
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parental Schizophrenia in the Development of Behavioral Disorders and Mental Illness in Children

Abstract: IntroductionParental schizophrenia will potentially cause dysfunction in mother-child relationships, and it will also cause difficulty in adapting to motherhood.ObjectivesWe aim to study the implications of the relationship between mothers with schizophrenia and their children. The psychosocial environment and the impact of dysfunctional relationship in social skills development may cause behavioral disorders in children and further development of severe mental illness taking into account genetic factors and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Offspring of a parent with schizophrenia was known to have difficulties in socio-emotional interactions that may persist into adulthood [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Offspring of a parent with schizophrenia was known to have difficulties in socio-emotional interactions that may persist into adulthood [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that most women with schizophrenia value their role as mothers. However, sometimes they feel that they may not able to competently play their role, and this may result in adverse consequences including the risk of poverty, substance abuse, domestic violence, social isolation or inadequate housing, and failure to teach social skills to children to name a few (Alves et al, 2017; Seeman, 2010). The process of psychological development of the child depends a lot on the social relations between the mother and child.…”
Section: Introductionmentioning
confidence: 99%